Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Connect with a community of experts ready to help you find solutions to your questions quickly and accurately. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
The solution of the given equation is :
cosθ = 1/2 when θ = π/3 + 2kπ or 5π/3 + 2kπ
cosθ = -1 when θ = π + 2kπ
Since cos2θ + sin2θ = 1, sin2θ = 1 - cos2θ
So, the given equation is equivalent to 2(1 - cos2θ) - cosθ = 1
-2cos2θ - cosθ + 1 = 0
2cos2θ + cosθ - 1 = 0 (multiplying the entire equation by -1)
(2cosθ - 1)(cosθ + 1) = 0 (taking common)
cosθ = 1/2 or cosθ = -1 (on equating it to zero)
cosθ = 1/2 when θ = π/3 + 2kπ or 5π/3 + 2kπ
cosθ = -1 when θ = π + 2kπ
For more information about trigonometric ratios, visit
https://brainly.com/question/24496175
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.